(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article presents in order to evaluate the effectiveness of the parabolic solar concentrator heliopyrolysis device developed, the indicators of natural gas consumption for domestic needs of households and consumers located far from energy supply (farmers and farms) were analyzed. Using a heliopyrolysis device with a parabolic solar concentrator, an average of 300÷350 m3 of gaseous fuel, 350÷400 kg of liquid pyrolysis fuel and 200÷300 kg of solid fuel per year for household needs of residents and consumers located far from the energy supply the availability of alternative fuels is scientifically based.